Investigating of the mediating role of social problems solving in the relationship among parental perception and psychological well-being of adolescences - Mahnaz Moradi; Maryam Koroushnia; Zahra Afrasbi (University of Hormozgan, 2022)
The aim of current study was to investigate the meditator role of social problems solving in the relationship between parental perception and psychological well-being through a correlational research. Statistical society included all students of the first secondary high school students in shiraz in 2022. For this purpose, 196 (100 male and 96female) students were selected using random cluster sampling, and social problem-solving ability competency was used to collect data. Inferential statistics test (Pearson correlation test and Path analysis) have been used to check the research hypothesis. The results of Baron Kenny's path analysis showed that social problems solving has a significant mediating role in the relationship between parental perception and psychological well-being. Mother cordiality, father's support for autonomy and social problems solving all have an impact on psychological well-being, but the components of parental involvement, support for mother's autonomy and father cordiality do not have a significant effect on psychological well-being.